2011
DOI: 10.1007/s12272-011-0712-0
|View full text |Cite
|
Sign up to set email alerts
|

Determining the difference in medication compliance between the general patient population and patients receiving antihypertensive therapy: A case study

Abstract: This study addressed the issue of medication compliance in general, compliance with antihypertensive therapy, and the relationship between these two groups. In addition to determining the reasons for noncompliance with therapy prescription, the aim of this study was to also establish whether it was considered feasible by the patients to comply with their physician's instructions and whether the patients believed that the prescribed therapy was beneficial to their health. Hypertensive patients were compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 22 publications
1
22
2
9
Order By: Relevance
“…In our study non-adherent subjects prevailed over adherent (64.0%) which is a slightly higher rate than that found in our previous study, where adherence was based on patient self-report (58.3%) 7 . A similar difference is found in non-adherence to cardiovascular and antihypertensive therapy in both studies (63.1 vs. 60.7%).…”
Section: Discussioncontrasting
confidence: 76%
“…In our study non-adherent subjects prevailed over adherent (64.0%) which is a slightly higher rate than that found in our previous study, where adherence was based on patient self-report (58.3%) 7 . A similar difference is found in non-adherence to cardiovascular and antihypertensive therapy in both studies (63.1 vs. 60.7%).…”
Section: Discussioncontrasting
confidence: 76%
“…In addition to the positive therapeutic effect, different side effects are associated with drug use. However, in our research it has been shown that persistent patients have statistically significantly fewer overall health problems than the unreliable ones 8 . It is important to warn the patient about any possible side effects, such as, for example, orthostatic hypotension in some antihypertensive agents, so as not to be disappointed with the effect of the drug and give up the prescribed medication.…”
Section: Discussioncontrasting
confidence: 51%
“…For example, despite the existence of highly effective antihypertensive drugs, some studies show that only 30% of patients in the United States achieve adequate blood pressure control 1 . In Zagreb, according to our research, it is somewhere below 40% 8 . Well-known high-risk complications of unregulated blood pressure are: 3-4 times greater chance of ischemic heart disease, and 3 times greater incidence of stroke 4 .…”
Section: Discussionmentioning
confidence: 64%
“…Forgetfulness is the most common reasons for not adhering to drug treatment (26). The key question is: Why do people forget?…”
Section: Pharmacist-family Physician Relationshipmentioning
confidence: 99%